Cooperation in a changing world: a discussion on new regionalism and globalisation - Bendebka, Ramzi (Modern Diplomacy, 2022)
The two main trends that have shaped the World Economic Order are 1) multilateralism, which sets global rules for international trade without favouritism, and 2) new regionalism, which sets up several zones of regional free trade and cooperation that can apply development and economic growth more quickly and flexibly but have a limited geographic scope.